Trunk Trouble - "Carter , Felicity " (Igloo)
"Trunk Trouble" is a children's book by Felicity Carter, illustrated by Karen Sapp. The story follows Little Elephant, who eagerly wants to play games with his friends but finds that his long trunk often causes mishaps during their activities. Through the narrative, Little Elephant learns to embrace his unique feature, discovering that his trunk can be advantageous and that being different is something to be celebrated